2009
DOI: 10.1002/ajpa.21193
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Efficiency of total demineralization and ion‐exchange column for DNA extraction from bone

Abstract: We investigated whether a combination of recently introduced methods, total demineralization and ion-exchange columns, would increase DNA recovery from old bone. Ten bone samples taken after a burial period of approximately 60 years were used in this study. Bone powder was digested using total or incomplete demineralization. DNA was extracted by the standard organic method. The DNA extract was purified with ion-exchange columns or QIAquick spin columns. The efficiency of different DNA extraction methods was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
(20 reference statements)
3
27
1
1
Order By: Relevance
“…Recent articles demonstrated that calcium ions inhibit Taq DNA polymerase (Opel et al, 2010) and demineralization improved DNA typing (Loreille et al, 2007;Seo et al, 2010). By increasing the digestion volume from 1.0 ml to 1.5 or 2.0 ml and using the Investigator kit Large Volume protocol, there was a resultant 60 and 38%, respectively, increase in DNA recovery over the buffer ATL 1 EDTA using the Trace protocol.…”
Section: Study 1: Selection Of Digestion Componentsmentioning
confidence: 99%
“…Recent articles demonstrated that calcium ions inhibit Taq DNA polymerase (Opel et al, 2010) and demineralization improved DNA typing (Loreille et al, 2007;Seo et al, 2010). By increasing the digestion volume from 1.0 ml to 1.5 or 2.0 ml and using the Investigator kit Large Volume protocol, there was a resultant 60 and 38%, respectively, increase in DNA recovery over the buffer ATL 1 EDTA using the Trace protocol.…”
Section: Study 1: Selection Of Digestion Componentsmentioning
confidence: 99%
“…The bones had been kept underground for several decades and thereafter stored at room temperature until analysis followed by the cleaning procedure [11]. Conventional autosomal STR and Y-STR analysis using commercial kits along with mitochondrial DNA typing were performed but failed to generate full STR profiles for the bone DNA samples.…”
Section: Case Reportmentioning
confidence: 99%
“…DNA was extracted using the QuickGene DNA Whole Blood Kit S with the QuickGene-Mini80 instrument (Kurabo, Osaka, Japan). Bone DNA was isolated from the chopped fragment of two femur bones through a phenol/chloroform extraction method [11]. The DNA concentration was measured using NanoDrop™ 2000 Spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Case Reportmentioning
confidence: 99%
“…Skeletal remains are able to preserve DNA for a long time . For that reason, they are often utilized for ancient archeological or anthropological DNA analysis or for identification of missing persons in, for example, mass disasters in forensic genetics . Mostly, short tandem repeats (STRs) are used for DNA typing.…”
mentioning
confidence: 99%